Adsorption of Cr(VI) from aqueous solution using residual coated sand (RCS) equilibrium, kinetic and thermodynamic studies - Ibe, Aldwin H. (College of Engineering, University of the Philippines Diliman, 2013)
The tanning industry is the largest contributor to worldwide toxic chromium pollution. In this study, silica and media coated with drinking water treatment (DWT) residual was applied to remove Cr (VI) from synthetic wastewater by batch adsorption process. Effects of adsorption parameters such pH (pH 2-6), temperature (298-318 K), initial Cr concentration (1-50 mg/L), adsorbent dosage (0.2-2.0 g/30 mL solution), contact time (10-180 min) and ionic strength (0-0.1 M KNO₃) on Cr (VI) removal were investigated. Adsorption capacities of residual coated sand (RCS) as a function of initial Cr concentration (1-50 mg/L) were fitted to adsorption isotherm models. Based on linear regression analysis (R²=0.9450) and non-linear chi-square test (x²=0.1330), Freundlich isotherm best describes Cr (VI) adsorption onto RCS, which suggests heterogeneity of RCS sorption sites. The highest RCS adsorption capacity at pH 4 was computed at approximately 271.50 mg/kg. High correlation of kinetic data with pseudo-second order model (R²>0.9808) and the high positive activation energy values (Ea = 22.7263 and 40.9531 kJ/mol) from 298-318 K indicate that chemisorption is the dominant rate controlling step of the adsorption process. Computed values for thermodynamic parameters of activation (ΔH*, ΔG*, and ΔS*) suggest that i) activation mechanism is endothermic, ii) external source is required for adsorption process to proceed and iii) no significant change in the internal structure of the adsorbent occurs during adsorption. The results of the study demonstrated the potential of RCS in removing Cr (VI) from industrial wastewater sources.